Experimental investigation on the microscopic characteristics of underexpanded transient hydrogen jets. (24th June 2020) - Zhao, Jianhui; Liu, Weilong; Liu, You
Abstract: The microscopic characteristics of hydrogen jet affect the concentration distribution and gas-air mixing of high-pressure gas jets for a hydrogen engine. In this study, the schlieren method was used to record the hydrogen jet for an outward-opening injector. The results showed that the jet asymmetricity was large in the initial stage of the jet development, then decreased rapidly as the jet developed, and finally entered a stable range of 13%–38% when the valve fully opened. The increase of the ambient pressure was beneficial to reduce the fluctuation range of the asymmetricity. The steady S of an outward-opening injector ( S = 0.7 ± 0.03) is larger than that of a single-hole injector ( S = 0.25 ± 0.05). The increase in injection pressure and the decrease in ambient pressure caused S to decrease to 1 faster. The steady Γ of an outward-opening injector was experimentally determined, and the value (Γ = 0.98 ± 0.1) was smaller than that of a single-hole injector. According to the transient Γ, the injection process can be divided into the developing phase and the self-similar phase. Γ increased rapidly with time and then stabilized after the injector valve reached its maximum lift position. The gas concentration distribution was uneven along the axial direction. The mole fraction decreased with the increase in axial penetration, and entered a stable range of 0.27–0.37 when axial penetration was greater than 20 mm. The average equivalent ratio was large at the beginning of injection under different pressure ratios, and then decreased and finally stabilized in the range of 1.4–5. Graphical abstract: Image 1 Highlights: The self-similarity characteristics of hydrogen jet were comprehensively evaluated. The steady Γ for an outward-opening injector was experimentally determined. The mechanism of the nonuniformity of gas concentration distribution was revealed.